O Distrito Industrial de Maracanaú/CE no contexto do regime de acumulação com dominância financeira: avaliação da política de renúncia fiscal no cenário da abertura econômica - Gomes, André de Souza (2022)
In the field of disputes in productive investments, constant movements emerge with the nickname of fiscal war between the federated entities (DF, states and municipalities). Regional deconcentration ventures have involved tax waivers for legal entities to be located in several Brazilian states. In this sense, we carried out this dissertation study with the general objective of evaluating the public policy of fiscal waiver, fostered in the Industrial District (DI), located in the city of Maracanaú/CE, in the context of the accumulation regime with financial dominance, from the neoliberal perspective. Regarding the specific objectives, they are divided into two, namely: to identify the socioeconomic impacts generated by the tax waivers of the Industrial District of Maracanaú and to understand the tax waiver as an aspect of the financialization of markets, through the neoliberal logic of the accumulation regime with financial dominance. As for the methodological path, the academic-scientific investigation resorted to the qualitative approach based on the in-depth evaluation proposed by Rodrigues (2008, 2011, 2016). Therefore, the investigative-academic-scientific itinerary is embodied in a multi-referential analysis, considering multiple dimensions, respecting the field of subjectivity of the social actors involved in the researched public policy. As for the methodological procedures, a documental research was used, through the exploration of material concerning the Brazilian legal system. In addition, immersion in bibliographic research was essential, given that this constitutes a condition sine qua non, for other types, forms and modalities of academic research. As collection instruments, we used the techniques of field observations and semi-structured interviews, through a previous script (in the appendix). In short, it is clear that this public policy has generated several questions regarding the application of resources, their privilege to industrial financial capital, to the detriment of public policies, in necessary areas such as health, education, public security and infrastructure.